The current state of transition metal-based electrocatalysts (oxides, alloys, POMs, and MOFs) for oxygen reduction, oxygen evolution, and hydrogen evolution reactions - Henrique Araújo; Henrique Araújo; Biljana Šljukić; Sandra Gago; Diogo M. F. Santos (Frontiers in Energy Research, 2024)
Climate change is showing its impacts now more than ever. The intense use of fossil fuels and the resulting CO2 emissions are mainly to blame, accentuating the need to develop further the available energy conversion and storage technologies, which are regarded as effective solutions to maximize the use of intermittent renewable energy sources and reduce global CO2 emissions. This work comprehensively overviews the most recent progress and trends in the use of transition metal-based electrocatalysts for three crucial reactions in electrochemical energy conversion and storage, namely, the oxygen evolution (OER), oxygen reduction (ORR), and hydrogen evolution (HER) reactions. By analyzing the state-of-the-art polyoxometalates (POMs) and metal-organic frameworks (MOFs), the performance of these two promising types of materials for OER, ORR, and HER is compared to that of more traditional transition metal oxides and alloy-based electrocatalysts. Both catalytic activity and stability are highly influenced by the adsorption energies of the intermediate species formed in each reaction, which are very sensitive to changes in the microstructure and chemical microenvironment. POMs and MOFs allow these aspects to be easily modified to fine-tune the catalytic performances. Therefore, their chemical tunability and versatility make it possible to tailor such properties to obtain higher electrocatalytic activities, or even to obtain derived materials with more compelling properties towards these reactions.